2018
DOI: 10.1089/jmf.2018.4246
|View full text |Cite
|
Sign up to set email alerts
|

Ginsenoside Rb1 Enhances Keratinocyte Migration by a Sphingosine-1-Phosphate-Dependent Mechanism

Abstract: The cutaneous wound healing process is tightly regulated by a range of cellular responses, including migration. Sphingosine-1-phosphate (S1P) is a signaling lipid produced in keratinocytes (KC) and it is known to stimulate skin wound repair through increased KC migration. Of the multifunctional triterpene ginsenosides, Rb1 enhances cutaneous wound healing process by increasing KC migration, but cellular mechanisms responsible for the Rb1-mediated increase in KC migration are largely unknown. Therefore, we hypo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 53 publications
1
11
0
Order By: Relevance
“…Pertinently, VPA treatment of seizure disorders in humans can also provoke often severe, cutaneous hypersensitivity reactions [56,57]. We show here further that characteristic AD-like, lipid biochemical features [58], likely induced by elevated IFNg levels [59][60][61], appear not only in the epidermis [62,63], but also in the brain. Together, these results explain the phenotypic overlap of these two disorders, while also supporting a new paradigm for disease pathogenesis in the subset of ASD patients associated with AD.…”
Section: Introductionsupporting
confidence: 66%
“…Pertinently, VPA treatment of seizure disorders in humans can also provoke often severe, cutaneous hypersensitivity reactions [56,57]. We show here further that characteristic AD-like, lipid biochemical features [58], likely induced by elevated IFNg levels [59][60][61], appear not only in the epidermis [62,63], but also in the brain. Together, these results explain the phenotypic overlap of these two disorders, while also supporting a new paradigm for disease pathogenesis in the subset of ASD patients associated with AD.…”
Section: Introductionsupporting
confidence: 66%
“…Immortalized, non-transformed (HaCaT) human keratinocytes (KC), derived from the human epidermis (a gift from N. Fusenig, Heidelberg, Germany), were grown as described previously [ 22 ]. Culture medium was switched to serum-free KC growth medium containing 0.07 mM calcium chloride and growth supplements (Thermo Fisher Scientific, Carlsbad, CA, USA) 1 day prior to the N-palmitoyl serinol (PS, Dr. Raymond Laboratories, Englewood Cliffs, NJ, USA) treatment.…”
Section: Methodsmentioning
confidence: 99%
“…Alterations in the epidermal ceramide content have been characterized in certain inflammatory skin diseases, including atopic dermatitis (AD) [4]. In AD skin lesions, the content of ceramides containing long-chain fatty acids (FAs) (22)(23)(24)(25)(26) carbons in length) is significantly reduced, whereas ceramides with shortchain FAs (<20 carbons in length) are conversely elevated, leading to compromised barrier integrity [4].…”
Section: Introductionmentioning
confidence: 99%
“…In another in vitro study by Lee et al, on human dermal fibroblasts, results showed that ginsenosides obtained from a Panax ginseng root extract exert a healing effect by increasing type I collagen synthesis through the activation of the Smad pathway; the antioxidant effect of the extract also contributes to the healing process [107]. In a more in-depth study of the mechanism of action of ginsenosides by Shin et al [108] it has been reported that the healing effect of ginsenosides is related to their property of increasing the migration of human keratinocytes through a sphingosine-1-phosphate (S1P) dependent mechanism. The data obtained by Shin et al support the hypothesis that ginsenosides act through the S1P pathway, noting that they increase S1P production by regulating the activity of enzymes associated with the generation and degradation of S1P [sphingosine kinase 1 and S1P lyase).…”
Section: Ginsenosidesmentioning
confidence: 99%